China, the European Union, and the International Politics of Global Governance
X, 290 p.
Keywords: Two major themes in contemporary international relations—Sino-European relations and global governance—are both addressed in this volume. In its focused analysis of Sino-European relations, global governance serves as both a topic for analysis and a conceptual framework to join together individual chapters. Featuring perspectives from a diverse group of established and promising young scholars from China, Europe, and elsewhere, this book has important implications for Chinese foreign policy, the European Union, the future of global governance, and international relations at large.